1989
DOI: 10.3109/10641968909045447
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Renal Production of Dopamine in Patients with Low Renin Essential Hypertension

Abstract: Our previous studies have shown that a suppressed pressure natriuresis may contribute to the hypertensive mechanism in patients with essential hypertension (EHT), particularly in low renin patients (LRH). In this study, in order to clarify the role of renal dopaminergic activity in the blunted natriuresis of LRH, the conversion of 1-dopa (DOPA) to dopamine (DA) in the kidneys was investigated in 9 normotensive subjects (NT) and 20 EHT, including 15 normal renin EHT (NRH) and 5 LRH. All subjects were hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…These EH patients were considered to be stable when their hypertension was consistently more than 160/95 mm Hg and their BP did not decrease (when medication had been stopped) to normotensive values after 4 days of bed rest. 3 They had been treated with all categories of antihypertensive drugs for up to 22 years. They stopped all medication at least 10 days (longer acting drugs, 3 weeks) before the examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These EH patients were considered to be stable when their hypertension was consistently more than 160/95 mm Hg and their BP did not decrease (when medication had been stopped) to normotensive values after 4 days of bed rest. 3 They had been treated with all categories of antihypertensive drugs for up to 22 years. They stopped all medication at least 10 days (longer acting drugs, 3 weeks) before the examination.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated an attenuated urinary dopamine response to salt in stable EH (s-EH) patients, 1 its probable cause suspected to be a deficient renal DOPA decarboxylation to dopamine. 2 This aspect was investigated by Aoki et al 3 in EH with an oral precursor load of DOPA in an attempt to at least partially reproduce patterns of defective renal dopamine generation from DOPA. However, the conclusions were based only on plasma DOPA and urinary dopamine measurements, without the determination of some intermediate steps between plasma DOPA and urinary dopamine, their respective metabolites, and blood pressure (BP) responses to exogenous DOPA.…”
mentioning
confidence: 99%
“…6 " 8 This has prompted us to examine the renal effects of dopamine in the Dahl salt-sensitive (DS) rat. The DS rat is extremely sensitive to the blood pressure elevation effect of a high salt diet 9 and exhibits impaired intrinsic natriuretic capacity.…”
mentioning
confidence: 99%
“…NHE activity was assayed as the initial rate of the Na ϩ -dependent pH i recovery, measured after an acid load imposed by 20 mM NH 4 Cl, followed by removal of Na ϩ from the Krebs modified buffer solution, in the absence of CO 2 /HCO 3 . In some experiments, SHR cells were cultured in permeable polycarbonate filters to access the apical NHE activity only.…”
Section: Resultsmentioning
confidence: 99%